DEVELOPMENT OF TEXT COMPREHENSION SKILLS OF PRIMARY SCHOOL STUDENTS - Madina Khusanova Askarovna (International Journal of Innovations in Engineering Research and Technology, 2023)
This article talks about the importance and status of the science of mother tongue and reading literacy, which are new generation textbooks taught in primary grades.